2016
DOI: 10.5604/17331331.1204480
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Parasitic Contamination in Salad Vegetables Collected from Supermarkets and Street Vendors in Amman and Baqa’a – Jordan

Abstract: A b s t r a c tOne of the main ways in transmitting parasites to humans is through consuming contaminated raw vegetables. The aim of this study was to evaluate the prevalence of parasitological contamination (helminthes eggs, Giardia and Entamoeba histolytica cysts) of salad vegetables sold at supermarkets and street vendors in Amman and Baqa'a -Jordan. A total of 133 samples of salad vegetables were collected and examined for the prevalence of parasites. It was found that 29% of the samples were contaminated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
18
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 29 publications
(30 reference statements)
5
18
1
2
Order By: Relevance
“…The current study showed a considerable high level of parasitic contamination of examined vegetables and fruits (39%) ( Table (2) showed the distribution of each parasitic contamination in various examined raw vegetables and fruits, where G. lamblia cysts were the most prevalent on lettuce samples (17.1%) followed by watercress (15.7%), parsley (14.2%), cucumber (11.4%), carrots (10%) and finally strawberry (7.1%). These results agree with a study conducted in Amman, Gordan [33] where lettuce samples were being the most contaminated (63%). In contrast, it was found in Libya that only 4% of lettuce was contaminated by G. lamblia cysts [10].…”
Section: Discussionsupporting
confidence: 92%
“…The current study showed a considerable high level of parasitic contamination of examined vegetables and fruits (39%) ( Table (2) showed the distribution of each parasitic contamination in various examined raw vegetables and fruits, where G. lamblia cysts were the most prevalent on lettuce samples (17.1%) followed by watercress (15.7%), parsley (14.2%), cucumber (11.4%), carrots (10%) and finally strawberry (7.1%). These results agree with a study conducted in Amman, Gordan [33] where lettuce samples were being the most contaminated (63%). In contrast, it was found in Libya that only 4% of lettuce was contaminated by G. lamblia cysts [10].…”
Section: Discussionsupporting
confidence: 92%
“…A portion (usually 50-250 g) of each vegetable or fruit sample is washed separately in a container containing some chemical solutions. The most widely used solutions are normal saline [14,[17][18][19][20] and phosphate-buffered saline [12,[21][22][23][24]. The commonly used solutions are glycine [11,25], sodium dodecyl sulfate [26], Alconox ® [27], and Tween 80 [28].…”
Section: Detection Methods Of Intestinal Protozoan Parasites Contaminmentioning
confidence: 99%
“…More than one smear slide is usually prepared for each specimen to allow its precise detection [12,26]. Oocysts or cysts can be detected microscopically based on their morphological features [14,17,20,29], using Lugol's iodine [12,14,29] or modified Ziehl-Neelsen staining (or any other staining technique) [14,19,26]. The extraction of the parasitic DNA from the sediment, followed by the PCR amplification of specific genes, is also efficiently used for the protozoan detection in vegetable and fruit samples [22,24].…”
Section: Detection Methods Of Intestinal Protozoan Parasites Contaminmentioning
confidence: 99%
“…Raw vegetable consumption often contributes to an epidemiological role in the transmission of parasitic food-borne diseases ( de W Blackburn and McClure, 2002 ; Eraky et al, 2014 ). Studies over the world have shown that many species of enteric helminthes and protozoa can infect humans who consume contaminated, improperly washed fruits and vegetables ( Al-Shawa and Mwafy, 2007 ; Adanir and Tasci, 2013 ; Ismail, 2016 ). Vegetables become contaminated with different parasitic phases (cyst, oocyst, ova, larvae) during irrigation by waste water or by direct contamination from animals and humans during harvesting, packing, transport processing, distribution, and marketing ( Amoah et al, 2007 ; Gabre and Shakir, 2016 ).…”
Section: Introductionmentioning
confidence: 99%